Semantic Commerce for Developing Country - Dewi Wisnu Wardani (IJID (International Journal on Informatics for Development), 2012)
The recent real challenges of semantic technology is not in the core of the technology but much more in implementing the semantic technology in the real problem. The common domain in any world is economics. One of the most important domain in economics is marketing. Company moreover small company from developing country desperated in increasing to make their company's product are known wider, around the world as well. Product from developing countries usually has a good quality, unique and cheaper but lack to be known. This paper present idea how semantic technology will give a benefit in marketing strategies for business in developing countries. The short goal is how the common famous search engine will be more understand the company both product and profile, thus present those information in better form and possible to the next processing in the others semantic technology.